Clinical aspects of egg bioactive peptide research: a review. (22nd February 2019) - Grootaert, Charlotte; Voorspoels, Stefan; Jacobs, Griet; Matthijs, Bea; Possemiers, Sam; Van der Saag, Hans; Van Camp, John; Lucey, Alice
Summary: Extensive in vitro and, to a more limited extent, animal research have demonstrated the health potential of a wide set of egg protein hydrolysates; however, well‐designed human intervention studies are scarce. Health claim assessment, however, sets high standards for characterisation of the bioactive peptides, investigation of the mode‐of‐action and convincing human intervention studies. In this review, we discuss the state‐of‐the‐art and knowledge gaps related to egg‐derived peptide bioavailability and bioactivity. In addition, we will formulate recommendations for appropriate design of future human intervention trials with egg‐derived peptides. Abstract : Egg‐derived bioactive peptides may impact cardiovascular and metabolic health. Although this was illustrated by many in vitro and animal experiments, human intervention studies are scarce and prone to high variability. This paper reviews critical parameters that may induce variability, and provides some advice to improve of the design of clinical trials using egg‐derived peptides.